Downward wage rigidity for different workers and firms: an evaluation for Belgium using the IWFP procedure - Philip Du Caju; Catherine Fuss; Ladislav Wintr (National Bank of Belgium, 2007)
This paper evaluates the extent of downward nominal and real wage rigidity for different categories of workers and firms using the methodology recently developed by the International Wage Flexibility Project (Dickens and Goette, 2006). The analysis is based on an administrative data set on individual earnings, covering one-third of employees of the private sector in Belgium over the period 1990-2002. Our results show that Belgium is characterised by strong real wage rigidity and very low nominal wage rigidity, consistent with the Belgian wage formation system of full indexation. Real rigidity is stronger for white-collar workers than for blue-collar workers. Real rigidity decreases with age and wage level. Wage rigidity appears to be lower in firms experiencing downturns. Finally, smaller firms and firms with lower job quit rates appear to have more rigid wages. Our results are robust to alternative measures of rigidity
Keywords: J31; 330; wage rigidity; matched employer-employee data.; Lohnrigidität; Niedriglohn; Lohnindexierung; Belgien